AWAKENING THE SPIRIT OF ENTREPRENEURSHIP: SOCIALIZATION OF UMKM AS A SERVICE EFFORT IN THE VILLAGE - Rita Hayati; Melyana R Pugu; Engelbertus Kukuh Widijatmoko; Al-Amin (Adiba Aisha Amira, 2024)
Entrepreneurial spirit is the main focus of MSME socialization in rural areas. The program aims to increase entrepreneurial spirit and capability among rural communities through campaigns and support for micro, small and medium enterprises. The socialization focuses on education, training, and collaboration to overcome barriers faced by MSME players, in order to help improve the economy and living standards of local residents. The research method in this study uses a literature study. The results show that, first, the level of entrepreneurial literacy and understanding among villagers is still low, leading to slow business development and lack of product innovation. Second, rural MSMEs face significant constraints in accessing capital and funding sources, due to the lack of collateral and adequate financial records as well as complex regulations. Third, the lack of collaboration between the government, private sector and communities is a barrier to supporting the development of rural MSMEs. Support in the form of entrepreneurship training programs, simplification of regulations, and provision of adequate infrastructure is urgently needed. Effective socialization of entrepreneurial opportunities to villagers has proven to be able to encourage the growth of entrepreneurial spirit. With continuous socialization, MSMEs in villages have great potential to develop into the backbone of the local economy, which in turn will contribute to improving the living standards of local communities.